Computer modelling of gibbsite crystallization. - Fleming, Sean D. (Curtin University, 1999)
This thesis documents the development and application of a computer model for gibbsite, an aluminium tri-hydroxide polymorph. In particular, the work has emphasized the idea of computer modelling techniques combining with ex- observations to provide greater insight than either could separately. Chapter One provides an overview and introduction to the fields of solid state chemistry, crystallization and computer modelling. These ideas are extended in Chapter Two to include a more detailed discussion of the theoretical principles behind the modelling in this project. The development of transferable oxalate and hydroxide potential models, intended primarily for sodium oxalate and gibbsite, is described in Chapter Three. Both ab initio hypersurface fitting and lattice fitting techniques were utilized, with an average structural fitting error of under two percent. In addition, the potentials were used to successfully reproduce several (related) crystal structures, thus establishing the quality of the model. In Chapter Four, the model for gibbsite was employed in generating equilibrium and growth morphologies. The equilibrium morphology was found to give excellent agreement with experiment, with all observed faces present. However, the importance of the prismatic planes is underestimated. Also discussed in the chapter is a method for predicting the phenomenon of crystalline twinning. This technique was successfully applied to a number of systems, including gibbsite and sodium oxalate. In Chapter Five, the equilibrium morphology calculations performed earlier were extended by probing the effects of cation incorporation on the habit of gibbsite. This study was conducted in order to provide a first step in estimating the role of the crystallizing solution. Calculations of the change in surface energy caused by the replacement of a surface proton with a cation from solution were made. Different crystal habits were constructed by applying a range of defect surface coverage values to each of the faces appearing in the morphology. The resulting defect morphologies were in excellent agreement with crystal habits commonly observed by experimentalists. Also, the work provided an explanation for the earlier underestimation of the prismatic faces. Chapter Six documents molecular simulations of solutions containing the major species known to be present in industrial and experimental Bayer liquors. The structuring in two solutions, one containing sodium hydroxide and the other potassium hydroxide, was probed by constructing graphs of the radial distribution functions. These plots indicated that a significant degree of ion pairing was occurring between the alkali metal cations (Na+ and K+) and the aluminate monomer ([Al(OH)4(subscript)]-). Furthermore, these cations were found to be acting as 'bridges' which stabilize multiple aluminate monomers, allowing them to form clusters. This data was used to assist in explaining vibrational spectra, and to postulate that clustering may be the origin of the fine particle suspensions noted during the induction period.